Myocardial Shortening in 3 Orthogonal Directions and Its Transmural Variation in Patients With Nonobstructive Hypertrophic Cardiomyopathy - Okada, Kazunori; Yokoyama, Shinobu; Abe, Ayumu; Yamada, Satoshi; Murai, Daisuke; Kaga, Sanae; Hayashi, Taichi; Mikami, Taisei; Nakabachi, Masahiro; Tsutsui, Hiroyuki; Iwano, Hiroyuki; Nishino, Hisao; et al. (Circulation Journal, 2015)
Background:Although longitudinal strain (LS) is known to be reduced in patients with hypertrophic cardiomyopathy (HCM), it has not been elucidated whether or not circumferential strain (CS) is reduced. We aimed to determine whether multidirectional and layer-specific myocardial strain is reduced in patients with nonobstructive HCM.Methods and Results:Speckle-tracking echocardiography was performed in 41 HCM patients and 27 control subjects. Segmental and global LS and CS were measured in the inner, mid, and outer layers. Global LS was significantly lower in the HCM group than in controls in the inner (−10.3±2.9 vs. −14.8±2.0%, P<0.001), mid (−8.7±2.6 vs. −13.8±1.9%, P<0.001), and outer (−7.2±2.6 vs. −11.9±1.9%, P<0.001) layers. Global CS was preserved in the inner layer (−23.8±4.7 vs. −24.3±3.3%, P=0.69) but reduced in the mid (−10.3±3.1 vs. −13.3±2.5%, P<0.001) and outer layers (−6.7±2.3 vs. −8.6±2.3%, P=0.002). Differences in CS between the inner and outer layers correlated with segmental relative wall thickness (r=−0.20, P=0.002). Furthermore, only the absolute value of global CS in the inner layer positively correlated with left ventricular ejection fraction (r=0.32, P<0.01) among these multidirectional and layer-specific strains.Conclusions:In patients with HCM, not only the LS in all layers but also CS in the mid and outer layers was reduced, presumably reflecting impaired myocardial function. In contrast, CS in the inner layer was preserved, being associated with maintenance of chamber function. (Circ J 2015; 79: 2471–2479)